Maize farmers acquire early maturity seed across production environments - Rutsaert, Pieter; Donovan, Jason A.; Willwerth, Hanna S.; Nabwile, Colleta; Michelson, Hope C.; Muthee, John (CGIAR System Organization, 2023)
The primary factor used by CIMMYT to distinguish seed product market segments for maize in East Africa is the production environment (i.e., where the crop is grown). For each environment, it was assumed that farmers used the maturity level suited for that environment. The largest segment, according to estimated area under cultivation is wet lower midaltitude, intermediate maturity, followed by wet upper midaltitude, late maturity; highlands, late to very-late maturity; and dry midaltitude, early maturity. This brief explores to what extent the maturity level of seed products purchased by farmers matches the production environment where they are sold. We collected a panel of maize-seed sales data from 722 agrodealers in Kenya during two short-rains seasons and three long-rains seasons in 2020–2022. These agrodealers were located across all four maize production environments. Results showed strong sales of early-maturity products across the production environments, especially during the short-rains season. The results suggest an opportunity for increased breeding investments in short-maturity maize seed products.